2018
DOI: 10.1111/cei.13190
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-based reagents to study the influence of the epigenome on gene expression

Abstract: SummaryThe use of epigenome editing is set to expand our knowledge of how epigenetic landscapes facilitate gene expression capacity within a given cell. As epigenetic landscape profiling in health and disease becomes more commonplace, so does the requirement to assess the functional impact that particular regulatory domains and DNA methylation profiles have upon gene expression capacity. That functional assessment is particularly pertinent when analysing epigenomes in disease states where the reversible nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…On the host side, this has resulted in a spectacular array of molecular immune mechanisms that limit the viral cycle by a range of different strategies. Several of these have come to light due to comparative genomic analysis and have subsequently been validated through biochemical studies [ 128 , 129 ]. These include disparate mechanisms such as the modification of cell-surface molecules to prevent attachment of the virus, targeting of viral nucleic acids by restriction and CRISPR/Cas systems, limiting essential metabolites such as NAD + by targeted degradation, apoptotic or self-targeting mechanisms that limit viral replication and spread by targeting the ribosome or inducing cell-suicide [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the host side, this has resulted in a spectacular array of molecular immune mechanisms that limit the viral cycle by a range of different strategies. Several of these have come to light due to comparative genomic analysis and have subsequently been validated through biochemical studies [ 128 , 129 ]. These include disparate mechanisms such as the modification of cell-surface molecules to prevent attachment of the virus, targeting of viral nucleic acids by restriction and CRISPR/Cas systems, limiting essential metabolites such as NAD + by targeted degradation, apoptotic or self-targeting mechanisms that limit viral replication and spread by targeting the ribosome or inducing cell-suicide [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the relationship between the epigenome and transcriptome in asthma, we employed a CRISPR-Cas9-based approach to recapitulate the epigenome of asthma BECs in human embryonic kidney (HEK293T) cells in vitro ( Lavender et al, 2018 ). HEKs were chosen because they do not express some of the genes upregulated in asthma ( CLCA1 , POSTN , SERPINB2 ) and as such mirror expression of healthy BECs.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we found that targeting of DERs within asthma-SEs at SERPINB2 did not result in induction of gene expression ( Supplementary Figure S1I ). Regardless, dCas9-based epigenome editing provides a tremendous tool to help clarify the functional consequences of asthma-associated changes in the epigenome ( Lavender et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of Cas9 → dCas9 leads to a protein that no longer has nuclease activity but a stable DNA binding domain, that can be targeted using sgRNAs. There are various options for epieffector domains, including VPR/VP64 transactivation domains, the DNA demethylating TET domain or DNMT3A domain [ 195 , 196 , 198 , 199 ].…”
Section: Epigenetic Mechanisms As Drug Targetsmentioning
confidence: 99%